Distinct Cortical Correlates of Autistic versus Antisocial Traits in a Longitudinal Sample of Typically Developing Youth - Wallace, Gregory L. (Society for Neuroscience, 2012)
In humans, behaviors associated with autism and antisociality, disorders characterized by distinct social impairments, can be viewed as quantitative traits that range from frank impairment to normal variation, as found in the general population. Neuroimaging investigations of autism and antisociality demonstrate diagnostically specific aberrant cortical brain structure. However, little is known about structural brain correlates of social behavior in nonclinical populations. Therefore, we sought to determine whether autistic and antisocial traits exhibit dissociable cortical correlates and whether these associations are stable across development among typically developing youth. Three hundred twenty-three typically developing youth (age at first scan: mean = 10.63, SD = 3.71 years) underwent anatomic magnetic resonance imaging (1–6 scans each; total = 742 scans), and provided ratings of autistic and antisocial traits. Higher autistic trait ratings were associated with thinner cortex most prominently in right superior temporal sulcus while higher antisocial trait ratings were associated with thinner cortex in primarily bilateral anterior prefrontal cortices. There was no interaction with age, indicating that these brain–behavior associations were stable across development. Using assessments of both subclinical autistic and subclinical antisocial traits within a large longitudinal sample of typically developing youth, we demonstrate dissociable neuroanatomic correlations that parallel those found in the frank clinical disorders of autism (e.g., superior temporal cortex) and antisociality (e.g., anterior prefrontal cortex). Moreover, these correlations appear to be established in early childhood and remain fixed into early adulthood. These results support the dimensional view of psychopathology and provide neural signatures that can serve as informative endophenotypes for future genetic studies.